Analisis Moral Knowing Siswa Tentang Merokok Untuk Membentuk Karakter Peduli Kesehatan dalam Pembelajaran Biologi - Ximenez Diaz, Rury Rimenta; Chastanti, Ika; Sari, Novi Fitriandika (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The problem of school-age children engaging in smoking is becoming an increasingly worrying issue. This phenomenon not only threatens children’s physical and mental health, but also has implications for their academic performance and future. Moral knowing as an initial aspect to shape the character of students. This study aims to analyze the level of moral knowing of junior high school students about smoking. This study is a qualitative research conducted at SMPN 2 North Rantau, Labuhanbatu Regency. The research subjects were teachers and students of SMPN 2 North Rantau totaling 110 students. Sampling technique using purposive sampling with case study method. Data collection techniques were carried out through interviews, observations and questionnaires. The results showed that the highest rate was in the Perspective taking indicator of 28%, followed by the Moral reasoning indicator of 25%, the Self knowledge indicator of 20%, the knowing moral value indicator of 15%, the decisions making indicator of 8% and the Moral knowing indicator of 4%. These findings indicate that moral knowledge (moral knowing) has an important role in shaping adolescent behavior, including smoking behavior